SOURCES OF PERSONAL ORIGIN ABOUT THE ACTIVITIES OF THE GERMAN EMBASSY IN MOSCOW IN 1918: LACK OF EVIDENCE - Lannik L.V. (Вестник Брянского государственного университета, 2023)
The policy of the German Empire in the East after the conclusion of the Brest Peace possessed a crucial importance for the course of the last campaign of the Great War and the escalation of the Civil War in Russia. For a number of reasons, it has been still understudied, that’s why particularly important are the question of clarifying the source situation and the problem of the prospects for expanding the existing base. The German emissaries in Moscow in 1918 can be divided into several groups: diplomats, military, economists and journalists. The analysis of their personal testimonies can give valuable results under considering the professional specifics and details of their stay in the RSFSR. The testimonies of two ambassadors (Mirbach and Helfferich) and their deputies (Ritzler and Bassewitz), as well as military attaches, would be of crucial importance, but for various reasons it should be stated that there is a clear shortage of memories or their deliberate distortion for the sake of the political conjuncture not only of the 1920s-1930s, but also of the 1950s-1970s. The chances for the significant replenishment of the sources are small, but further work is needed to clarify the composition of the Kaiser’s missions in the RSFSR, and a careful selection of preserved materials could provide the subsequent introduction into the actual pool of sources of Russian historiography. The complementing of the source base would be a basic condition for creating a refined history of Soviet-German relations at their first stage, which could be an important step towards a genuine historicization of the events of 1918 in the former Russian Empire.